“influencia del potencial de hidrogeno (ph) y la granulometría sobre el ratio de concentración y él porcentaje de recuperación de oro (au), plata (ag) y cobre (cu) en la flotación de un mineral tipo sulfuro con alto contenido de plata” - Laiza Cueva, Frank Hebert (2016)
The flotation of sulfide mineral type with high silver content and the presence of As and Sb were studied. The mineral presented as chemical analysis 5.10 g/TM gold, 700.00 g/TM Ag, 3.9 % copper, 2.0 % of 1.2 % arsenic and antimony. The independent variable was considered the grain size in 3 levels: 55 % - #200, 60 % - #200, 65 % - #200. The other independent variable was the pH at 3 levels: 8.5, 10 and 11.5. The dependent variable was the percentage recovery of gold, copper and silver; and variable concentration ratio. The results show that if the pH is raised higher percentage copper recovery and increased concentration ratio is obtained, however decreases the percentage recovery of gold and silver, the particle size is observed that only affects the percentage recovery of copper and the concentration ratio. We conclude that pH significantly influences the rate of recovery of copper, gold, silver and the concentration ratio with a confidence level of 95 %. Obtaining the highest recovery of copper 61.67 % Cu at pH 11.5 and 65 % grain - #200, to the highest gold recovery of 59.51 % Au was obtained at pH 8.5 and 60 % grain - #200, for silver 79.45 %recovery at pH 8.5 and 65 % - #200 was obtained.